From discourse to enuciation - DADI, Hamza; IDRISSI AYDI, Ouafae (Revue Internationale du Chercheur, 2025)
Abstract The enunciative approach to language emphasizes the idea that every enunciative act rooted in “who is speaking to whom here and now” contributes to redefining what language is: not a pre-constructed abstract domain, but a permanent, interacting construction. Enunciation is always present, in one way or another, within the utterance; the different forms of this presence, and the degrees of its intensity, provide the basis for a typology of discourses. The aim of this article is to shed light on the work on enunciation, which made an important contribution to the development and emergence of discourse analysis in the 1950s. This work paved the way for the study of discourse and the way in which speakers inscribe themselves within it.